2019
DOI: 10.1080/21691401.2019.1576705
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release paclitaxel-loaded core-shell-structured solid lipid microparticles for intraperitoneal chemotherapy of ovarian cancer

Abstract: (2019) Sustained release paclitaxelloaded core-shell-structured solid lipid microparticles for intraperitoneal chemotherapy of ovarian cancer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Among them, PNCs, as polymer-based drug delivery systems prepared from biodegradable and biocompatible polymers, represent the promising formulations in cancer therapy (Pandey and Khuller 2004;Liechty et al 2010;Nicolas et al 2018;Fontana et al 2014;Sengel-Turk et al 2018;Yang et al 2016;Nan 2019;Bou et al 2020). The advantages of PNCs include the high capacity of drug loading, physicochemical stability, protection against enzymatic degradation due to the presence of the polymeric media, appropriate pharmacokinetic properties, and high drug encapsulation efficiency (Chan et al 2009; Elsabahy and Wooley 2012; Remaut et al 2007;Mandal et al 2013;Han et al 2019). The polymers such as polyethylene glycol (PEG), poly(D,L-lactide) (PLA), poly(D,L-glycolide) (PLG), and their copolymers poly(lactide-co-glycolide) (PLGA) are examples of biodegradable polymers, which are used most often to prepare PNCs (Nie et al 2017;Weng et al 2020;Gomes et al 2019;Dimer et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, PNCs, as polymer-based drug delivery systems prepared from biodegradable and biocompatible polymers, represent the promising formulations in cancer therapy (Pandey and Khuller 2004;Liechty et al 2010;Nicolas et al 2018;Fontana et al 2014;Sengel-Turk et al 2018;Yang et al 2016;Nan 2019;Bou et al 2020). The advantages of PNCs include the high capacity of drug loading, physicochemical stability, protection against enzymatic degradation due to the presence of the polymeric media, appropriate pharmacokinetic properties, and high drug encapsulation efficiency (Chan et al 2009; Elsabahy and Wooley 2012; Remaut et al 2007;Mandal et al 2013;Han et al 2019). The polymers such as polyethylene glycol (PEG), poly(D,L-lactide) (PLA), poly(D,L-glycolide) (PLG), and their copolymers poly(lactide-co-glycolide) (PLGA) are examples of biodegradable polymers, which are used most often to prepare PNCs (Nie et al 2017;Weng et al 2020;Gomes et al 2019;Dimer et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Five of the eight tested mice died after receiving a 2 mg/kg dose of free verteporfin, whereas an intravenous injection of 8 mg/kg NLC-verteporfin significantly suppressed the growth of tumors without causing any obvious toxicity effects. Recently, Han et al (2019) created SLNs loaded with paclitaxel for the intraperitoneal treatment of OC. Data showed that the cytotoxicity of paclitazel loaded solid lipid microparticles (PTX-SLMPs) was significantly increased as compared to Taxol ® in SKOV-3 OC cells.…”
Section: Nanotechnology Approaches In Oc Treatmentmentioning
confidence: 99%
“…These innovative structures play an important role in designing dosage forms with required attributes for the pharmaceutical industry. Core-shell particles can aid in formulating dosage forms for several purposes including; protecting actives from degradation (stomach acidity) , an array of release profiles for example, immediate release [152], targeted release [153], and sustained release [154] or co-delivery of different actives [155]. For instance, a fast onset dosage form can be designed by ensuring an immediate release of the active by coating it with a thin layer of fast-dissolving polymeric shell [152].…”
Section: Matrix Systemsmentioning
confidence: 99%
“…For instance, a fast onset dosage form can be designed by ensuring an immediate release of the active by coating it with a thin layer of fast-dissolving polymeric shell [152]. In contrast, a sustained dosage form can be obtained using a slowly degrading solid lipid shell [154]. Moreover, a delayed onset dosage form with a targeted therapeutic action can be attained by coating the core structure with a responsive polymer that only dissolves at the required site of action under the response of physiological stimuli [144].…”
Section: Matrix Systemsmentioning
confidence: 99%